2016
DOI: 10.3892/ol.2016.4848
|View full text |Cite
|
Sign up to set email alerts
|

Matrine-induced autophagy counteracts cell apoptosis via the ERK signaling pathway in osteosarcoma cells

Abstract: Abstract. The aim of the present study was to observe whether autophagy was induced by matrine, and to investigate the role of autophagy in the antitumor effects of matrine on human osteosarcoma MG-63 cells and its underlying mechanism. MG-63 cells were cultured in vitro in matrine at a concentration of 0.6, 0.8, 1.0 and 1.2 g/l for 0, 24, 48 and 72 h. A MTT assay was used to evaluate the proliferation inhibition of MG-63 cells by matrine, and Annexin V-fluorescein isothiocyanate/propidum iodide (PI) staining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…Autophagosome formation is mediated by conjugation systems composed of ATG proteins, which culminate in the conjugation of ATG12 to ATG5 and conversion of a soluble form of microtubule‐associated protein 1 light chain 3 (LC3‐I) to another bound form, LC3‐II. Thus, the ratio of LC3II/LC3I is a marker of autophagy in some studies . Compared to the SNL group, the ratio of LC3II/LC3I was lower in the sham group but was significantly higher in the metformin treatment group (Figure B,C).…”
Section: Resultsmentioning
confidence: 89%
“…Autophagosome formation is mediated by conjugation systems composed of ATG proteins, which culminate in the conjugation of ATG12 to ATG5 and conversion of a soluble form of microtubule‐associated protein 1 light chain 3 (LC3‐I) to another bound form, LC3‐II. Thus, the ratio of LC3II/LC3I is a marker of autophagy in some studies . Compared to the SNL group, the ratio of LC3II/LC3I was lower in the sham group but was significantly higher in the metformin treatment group (Figure B,C).…”
Section: Resultsmentioning
confidence: 89%
“…Matrine exhibits a wide range of pharmacological effects and has long been applied to treat viral hepatitis (6), neuropathic pain (7), isoproterenol-induced cardiotoxicity inflammatory and other diseases (8,9). In addition, increasing evidence has revealed that matrine displays anticancer effects in various cancers, such as gastric (10), rhabdomyosarcoma (11), acute myeloid leukemia (12), osteosarcoma (13), prostate (14), breast (15) and lung cancer (16). Moreover, the antitumor mechanisms of matrine have been demonstrated to involve the blockade of cell cycle progression, the induction of apoptosis, the regulation of oncogene expression, the inhibition of cytokine production and the modulation of signaling pathways (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed that it has antitumor activity in various cancers such as, hepatocellular carcinoma (12), breast cancer (13), osteosarcoma (14), and RMS (15). Intensive studies confirmed the anti-tumor mechanisms of matrine, including regulation of phosphorylation of proliferation-and apoptosis-related cell signaling molecules such as β-catenin, serine/threonine kinase (AKT), mammalian target of rapamycin (mTOR), and ERK (16).…”
Section: Introductionmentioning
confidence: 99%